MIXED ABILITY CLASSES IN EFL LEARNING: PROBLEMS AND SOLUTIONS - Diana Luspa (Universitas PGRI Palembang, 2018)
Abstract: Every learner has his own learning style, linguistic background knowledge or individual face of learning and developing. Therefore, the majority of foreign language classes involve students of varying abilities. One class can consist of learners who display a number of differences in their learning abilities, motivation, previous exposure to learning, learning style, personality, attitude, and hundred thousands other features that anyone can think of . The situation becomes one challenge for many ESL/EFL teachers in teaching mixed ability classes. This emerges some educators to differentiate the instructions, set grouping strategies, create well structured cooperative activities and integrate meaningful content for the learners who may struggle with first and second language literacy skills. Therefore, if the teacher wants to ensure that all students perform to their maximum potential, the teacher must identify these problems and deal with them accordingly.